2023
DOI: 10.1113/jp284376
|View full text |Cite
|
Sign up to set email alerts
|

What if muscle spindles were also involved in the sense of effort?

Abstract: Effort perception is widely acknowledged to originate from central processes within the brain, mediated by the integration of an efference copy of motor commands in sensory areas. However, in this topical review, we aim to challenge this perspective by presenting evidence from neural mechanisms and empirical studies that suggest that reafferent signals from muscle spindles also play a significant role in effort perception. It is now imperative for future research (a) to investigate the precise mechanisms under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The magnitude of the motor command, and the subsequent corollary discharge, correspond to the degree of perception of effort [77][78][79]. Conversely, peripheralists argue that perception of effort is produced by integrating sensory information from numerous physiological systems rather than the brain alone [71,74,[80][81][82]. Despite these differences, our framework aligns with both views.…”
Section: Mechanisms Of Perception Of Effortmentioning
confidence: 73%
“…The magnitude of the motor command, and the subsequent corollary discharge, correspond to the degree of perception of effort [77][78][79]. Conversely, peripheralists argue that perception of effort is produced by integrating sensory information from numerous physiological systems rather than the brain alone [71,74,[80][81][82]. Despite these differences, our framework aligns with both views.…”
Section: Mechanisms Of Perception Of Effortmentioning
confidence: 73%
“…Indeed, it has recently been suggested that proprioceptive feedback does contribute to the maintenance of spinal realignment 14 . Moreover, it has been repeatedly suggested that muscle spindles may contribute to the sense of effort, heaviness or force [43][44][45][46][47] . While it has been unclear how muscle spindles may provide a continuously reliable muscle force signal 47,48 , it has been speculated that neural control based on alpha-gamma co-activation may aid in this purpose 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been repeatedly suggested that muscle spindles may contribute to the sense of effort, heaviness or force [43][44][45][46][47] . While it has been unclear how muscle spindles may provide a continuously reliable muscle force signal 47,48 , it has been speculated that neural control based on alpha-gamma co-activation may aid in this purpose 44 . We propose that, via compression of the spindle capsule, muscle spindles can encode press force and IMP in particular, with the latter known to be a more reliable index of muscle force than muscle electrical activity 4,5 .…”
Section: Discussionmentioning
confidence: 99%